2003
DOI: 10.1182/blood-2003-02-0663
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of hematopoietic progenitor cells in healthy volunteers by AMD3100, a CXCR4 antagonist

Abstract: Stromal cell-derived factor 1 (SDF1/ CXCL12) and its cognate receptor, CXCR4, play key regulatory roles in CD34 ؉ cell trafficking. We investigated whether AMD3100, a selective CXCR4 antagonist, could mobilize hematopoietic progenitor cells from marrow to peripheral blood in healthy human volunteers. Initially, 10 persons each received a single dose of AMD3100 (80 g/kg subcutaneously), which induced rapid, generalized leukocytosis associated with an increase in peripheral blood CD34 ؉ cells, representing pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
514
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(548 citation statements)
references
References 26 publications
23
514
1
10
Order By: Relevance
“…Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC. 34,89,90 AMD3100 (recently re-named as Plerixafor or Mozobil) is now owned by Genzyme Corporation (Cambridge, MA, USA) after a recent takeover of AnorMED by Genzyme in late 2006. Plerixafor is currently used in phase III trials in lymphoma and multiple myeloma patients undergoing autologous stem cell mobilization, and current plans are to file for US and European approval of the drug in 2008.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
“…Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC. 34,89,90 AMD3100 (recently re-named as Plerixafor or Mozobil) is now owned by Genzyme Corporation (Cambridge, MA, USA) after a recent takeover of AnorMED by Genzyme in late 2006. Plerixafor is currently used in phase III trials in lymphoma and multiple myeloma patients undergoing autologous stem cell mobilization, and current plans are to file for US and European approval of the drug in 2008.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
“…In pre-clinical settings, CXCR4 antagonists significantly reduced the size of primary tumors and had anti-metastatic effects in mouse models of melanoma, osteosarcoma, breast and prostate tumors [123][124][125][126][127]. AMD3100 was unexpectedly found to mobilize CD34+ stem cells from the bone marrow [128]. This compound is currently in clinical use for the mobilization of normal hematopoietic stem cells.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Early studies with plerixafor showed enhancement of circulating WBCs and PBSCs in healthy volunteers. [1][2][3][4] Flomenberg et al 5 showed the superiority of plerixafor plus G-CSF over G-CSF alone for PBSC mobilization in patients with multiple myeloma (MM) and non-Hodgkin's lymphoma (NHL). When apheresis yields for the same patient were compared between plerixafor plus G-CSF and G-CSF alone, more CD34 þ cells were collected with plerixafor plus G-CSF and in fewer apheresis days than with G-CSF alone.…”
Section: Introductionmentioning
confidence: 99%